Utilization of Environment-Based Science Learning Resources Around Sungai Pedada as Elementary Schools in the 3T Region of Indonesia - Rohana; Elsi Adelia Fitri Astuti; Yusni Arni (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The Pedada River is one of the 3T areas which is a coastal area located in South Sumatra Province. Its existence on the coast makes this area vulnerable to natural disasters such as tidal floods, and others. This study aims to analyze science learning resources as one of the 3T regions of Indonesia. This study uses a qualitative descriptive method. The data collection instruments used are questionnaires for students, interview guidelines for teachers, and analysis of teaching material documents. Based on the results of the needs analysis questionnaire, it shows that students are only facilitated by using the main textbook during classroom learning activities, the lack of use of learning media and other innovations in learning makes students not have great motivation in learning. Class-based learning activities are often constrained by natural conditions and road access from settlements to schools. The results of the interviews showed that teachers did not have the right experience in utilizing the surrounding environment as a potential for learning outside the classroom and still needed support in the provision of varied teaching materials. Thus, it can be concluded that learning resources at Sungai Pedada Elementary School are still very much needed and there is a need for training to improve teacher competence in developing teaching materials that are suitable for the student environment.